Crown lengthening and restorative procedures in the esthetic zone. Issue 1 (1st March 2018) - Marzadori, Matteo; Stefanini, Martina; Sangiorgi, Matteo; Mounssif, Ilham; Monaco, Carlo; Zucchelli, Giovanni
Abstract: Crown lengthening is one of the most common surgical procedures in periodontal practice. Its indications include subgingival caries, crown or root fractures, altered passive eruption, cervical root resorption and short clinical abutment, and its aim is to re‐establish the biologic width in a more apical position. While the procedure in posterior areas of the dentition has been thoroughly investigated, crown lengthening performed for esthetic reasons in the anterior areas is still a matter of debate and an evidence‐based technique is not available. This paper provides accurate descriptions of the surgical and restorative phases of the esthetic crown‐lengthening procedure by answering the following questions: what is the ideal surgical flap design? how much supporting bone should be removed? how should the position of the flap margin relate to the alveolar bone at surgical closure? and how should the healing phase be managed in relation to the timing and the position of the provisional restoration with respect to the gingival margin?